ANALYSIS OF THE IMPLEMENTATION OF THE ARCHIVAL RETENTION SCHEDULE POLICY: Digital Archives in The Secretariat General of The House of Representatives, Republic of Indonesia - Yusrina Malisi; Asropi Asropi (DIA: Jurnal Administrasi Publik, 2025)
The Secretariat General of The House of Representatives of the Republic of Indonesia (Setjen DPR RI) faces challenges in implementing the digital archive reduction policy by the Archive Retention Schedule. Issues in implementing the digital Archive Retention Schedule reduction have resulted in full data storage servers and increased costs for purchasing new data storage. This writing aims to identify and analyze the factors hindering the optimization of the implementation of the digital archive retention schedule policy at Setjen DPR RI. This research uses a qualitative method. The implementation of the electronic/digital records retention schedule policy at the Secretariat General of the House of Representatives (DPR RI) is not yet optimal due to several factors. These include challenges in human resources/archivists, a lack of communication and coordination between archivists, Pustekinfo, and the archive-managing work units, as well as 249 applications developed with non-integrated data. Additionally, the archivists have very limited time, and there is insufficient oversight from the National Archives (ANRI) in implementing the records retention schedule policy, particularly for electronic/digital records.